The immobilization and translocation of wild Asian elephant, Elephas maximus, in Peninsular Malaysia - Jainudeen, Mohamed Razeen; Mohamed Khan, (Persatuan Doktor Veterinar Malaysia, 1977)
The drug immobilization technique for the capture and translocation of wild elephants [Elephas maximus) is described. Doses of 2.7 mg to 8.6 mg of etorphine hydrochloride alone or in combination with acepromazine satisfactorily immobilized 9 out of 11 animals. Two capture related deaths were recorded. This technique proved to be safe and was a very practical method for elephants located in the dense vegetation and swampy conditions in Malaysia